1983
DOI: 10.1017/s0016756800027242
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism forming silicic segregations from basaltic magma discovered in igneous rocks of Western Sicily

Abstract: Summary. Mechanisms forming silicic segregations from basaltic magmas are considered of primary importance when dealing with magmatic problems. However, the processes which give rise to silicic segregations from basaltic magmas are so far obscure. Fortunately, the discovery of spheroidal felsic masses in some basic rocks of Western Sicily throws light on this subject. To clarify the relationships between felsic and basic fractions particular attention has been paid to the interactions which occurred at their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Phase separation in magma. Recently, Lucido [191] suggested that the texture of Sicilian magma may be explained by colloidal aggregation (or phase separation). He showed that it is possible that the Sicilian magma split into two liquid portions, one (basaltic) enriched in high-charge ions like iron, magnesium and calcium and the other (felsic) enriched in elements (Si, Al, Na and K) having the tendency to concentrate in the networklike structure.…”
Section: Roles Of Viscoelastic Phase Separation In Naturementioning
confidence: 99%
“…Phase separation in magma. Recently, Lucido [191] suggested that the texture of Sicilian magma may be explained by colloidal aggregation (or phase separation). He showed that it is possible that the Sicilian magma split into two liquid portions, one (basaltic) enriched in high-charge ions like iron, magnesium and calcium and the other (felsic) enriched in elements (Si, Al, Na and K) having the tendency to concentrate in the networklike structure.…”
Section: Roles Of Viscoelastic Phase Separation In Naturementioning
confidence: 99%
“…model is supported by the fact that: 1) the Sicilian ocelli are clearly richer in Si, Al, K and Na and are poorer in iron, mag nesium, calcium, manganese, titanium and phosphorus than the enclosing basaltic rock (see LuciDO, 1981). 2) at the moment of immiscibility much of the Sicilian magma was in a state of intensive (an unstable melt) (see LUCIDO, 1983). the Sicilian rock-samples exhibit regularity of spacing between the felsic clusters (Fig.…”
Section: Petrological Applicationmentioning
confidence: 96%
“…This is formed essentially by titanaugite, kaersutite, andesine, K-feldspar, analcite and zeolites. Previous studies (LucIDO, 1981(LucIDO, , 1983 Spinodal decomposition and metastable im miscibility are phenomena of considerable im portance in the glass industry (e.g., CAHN, 1968;SEWARD et al, 1968;DOREMUS, 1973;TEWHEY and HESS, 1974;LAUGHLIN and CAHN, 1975;ZDANIEWSKI, 1975;ALLEN andCAHN, 1976, LAUGHLIN, 1976). However, in contradistinction to the importance in glassy systems, these phenomena are underestimated from the geo logical point of view.…”
Section: Petrographical Observations Pertaining To Sicilian Rocksmentioning
confidence: 99%